Síntese e caracterização de compostos obtidos por moagem de alta energia do sistema Fe-Mn2O3 - Luciano, Arquimedes (2004)
Ceramic compounds were prepared starting from the mechanical processing of the system Fex(Mn2O3)1-x in mill of balls of high energy, in the interval of nominal compounds of 0.00 <_ X <_ 0.70. A series of samples was synthesized mechanically in free atmosphere (air) and other series in inert atmosphere (argon). The compounds were characterized by X-ray difratometry, Mössbauer spectroscopy and magnetization. The results reveal the formation of the spinel of iron-manganese for samples with the smallest initial concentrations of iron, and of the manganowustite for concentrations intermediate or majority of iron. It was observed, also, that the presence of available oxygen in the grinding vase delays the formation of the manganowustita, relatively to the inert atmosphere, but it makes possible a structural transition in the oxide manganese pure of the phase α for the phase γ.